2013
DOI: 10.1259/dmfr.20130121
|View full text |Cite
|
Sign up to set email alerts
|

Could standardizing “commercial off-the-shelf” (COTS) monitors to the DICOM part 14: GSDF improve the presentation of dental images? A visual grading characteristics analysis

Abstract: Objectives:To investigate whether standardizing commercial off-the-shelf (COTS) display devices to the digital imaging and communications in medicine part 14: greyscale standard display function (DICOM part 14: GSDF) would affect the presentation of dental images.Methods:Two COTS display devices from the radiology department of a dental teaching hospital and a laptop computer monitor for reference were calibrated to conform to DICOM part 14: GSDF. Four dental surgeons and two final-year students undertook a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Most of current published research pertaining to medical radiology has evaluated the performance of medical grade displays. From a thorough search of the literature only six studies evaluated commercial grade displays according to the aforementioned standards . However, to the best of the author's knowledge, this is the only study that has assessed the performance of a number of commercial grade displays according to DICOM part 14 GSDF and all primary and secondary acceptance standards established by the AAPM TG18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of current published research pertaining to medical radiology has evaluated the performance of medical grade displays. From a thorough search of the literature only six studies evaluated commercial grade displays according to the aforementioned standards . However, to the best of the author's knowledge, this is the only study that has assessed the performance of a number of commercial grade displays according to DICOM part 14 GSDF and all primary and secondary acceptance standards established by the AAPM TG18.…”
Section: Discussionmentioning
confidence: 99%
“…found a statistically significant reduction in observer performance with displays demonstrating lower contrast ratio and maximum luminance levels below the AAPM TG18 recommendations. McIllgorm et al . found that upon calibration of three standard office grade displays to DICOM part 14 GSDF standards, a statistically significant improvement in the perception of subtle contrast in images was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the observers and criteria used in this investigation, a high fidelity DICOM part 14: GSDF-calibrated COTS monitor produced an equally preferred perceived image quality to that of the DICOM part 14: GSDF-calibrated medical grade monitor when displaying an 8-bit dental image, and may also suggest that a DICOM part 14: GSDF-calibrated monitor can improve image presentation for the clinical observer. 10 Of course the limitation of visual grading as used in this Medical grade vs COTS investigation is that it is a subjective method to measure the difference in image quality between modalities and not a measure of the ability to make the correct diagnosis. Whether monitors that can support higher bit depths or calibrating a COTS monitor to the DICOM part 14: GSDF has any effect on clinical diagnosis, particularly with the availability of window levelling and image processing tools that can enhance the presentation of the image for diagnostic purposes, 15-17 may require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The method used for the relative VGA was similar to that previously described in the literature. 9,10 The manufacturers' names on the display devices were obscured, and the ambient lighting was set to between 25 and 40 lux. 11 The evaluation of the test monitors was alternated for each observer, and each observer scored one monitor against the reference monitor and then immediately scored the second monitor against the reference monitor; although for this evaluation, the sequence of the displayed images was changed.…”
Section: Selection Of Monitorsmentioning
confidence: 99%